Elective Courses in Global Surgery for Undergraduate Medical Students: A Narrative Review and a Proposal for European Universities - Rossi, Giovanni; Fusato, Gioele; Scirocco, Tindara; Rodi, Paolo; Villa, Simone; Raviglione, Mario C. B. (International Journal of Medical Students, 2023)
Global surgery (GS) is the discipline of improving health by expanding universal access to surgical care. GS is an essential part of the global health (GH) concept, but it is almost invariably neglected in academic settings. This review assesses the engagement of undergraduate medical students in the field of GS. PubMed, Embase, and Web of Science were searched with focus on electives organized by universities and only eight results were found. The scientific literature on this topic is scarce and uneven, and the number of students involved in these experiences is considerably low. Although few, the existing electives prove that building sustainable and useful GS projects is possible and that both students from high-income countries (HICs) and low-income and middle-income countries (LMICs) can extensively benefit from these experiences. Given the currently low involvement of European universities and medical schools, of which the authors are part, this review aims at encouraging European universities to organize GS electives for their students. In addition, this review suggests key activities to undertake in such electives including theoretical sections, research projects, and bilateral international rotations between HICs and LMICs.